Auditoría de gestión y su incidencia en el costo de producción del depósito de madera “san miguel”, cantón Quevedo, año 2013 - Chevez Castro, Gregoria Nataly (2015)
The purpose of this research work is based on the implementation of a management audit with an impact on the cost of production to the lumberyard San Miguel, Quevedo Canton, and performed in order to evaluate the efficiency, effectiveness and efficiency of the organization to check for proper compliance with the goals and objectives set by Management. It was made due to the need for Auditing by regarded as vital to the management element to provide key information on the fulfillment of the corporate objectives, and help solve economic, social and ecological problems through proper decision making . Also to be properly used production costs, because these help maintain business and are heavily involved in obtaining the resources of a manufacturing company and are involved in all the processes used for the productivity of an organization as they are : human talent, financial resources, technological resources, raw materials, among others. The research was conducted to gather the necessary information and carry out the Auditing was exploratory, descriptive and explanatory. Use of primary and secondary information, primary information was made as interviews, surveys, observation and own company records. On the other hand secondary information such as books, documents and Internet use it is presented. Using the techniques and audit procedures, we managed to capture the reality of the company in the working papers that are the basis of the results that are subsequently presented to adequately provide an opinion on the audit report also analyzed and found to Company operations are carried out with a well established legal basis to obtain a level of 90% Compliance, Internal Control risks are detected, the same as obtained 35% Equity risk, Risk Control 23% 15% Risk Detection and 1.21% Risk Audit to provide a tool for the management of the production area where the causes and weaknesses that can affect it and take the necessary measures to eradicate deepen.